DOP57 Monitoring response to anti-TNF therapy in ulcerative colitis patients by gastrointestinal ultrasound: sub-analysis from TRUST&UC. (25th January 2019) - Maaser, C; Petersen, F; Helwig, U; Fischer, I; Rath, S; Kolterer, S; Lang, D; Kucharzik, T
Abstract: Background: In ulcerative colitis GIUS (GastroIntestinal UltraSound) is discussed to be a reliable surrogate parameter for inflammatory activity next to faecal calprotectin (FC), and to some extend C-reactive protein (CRP). Treat to target (T2T) is an emerging concept of IBD management, which might lead to superior outcomes with regard to mucosal healing, steroid-free remission, and hospitalisation as shown with anti-TNF therapies in previous studies. 1 To ensure a stringent T2T approach, it is crucial to facilitate non-invasive, inexpensive, and reliable diagnostics to monitor disease activity. Recently, we published a multi-centre study evaluating the capability of GIUS to monitor therapy response in Crohn's disease patients. 2, 3 Here we provide a first subgroup analysis of the TRUST&UC study (TRansabdominal UltraSonography of the bowel To monitor disease activity in subjects with ulcerative colitis) focussing on the monitoring of anti-TNF therapy response in ulcerative colitis patients. Methods: In this sub-analysis of TRUST&UC, a prospective, observational multi-centre study, GIUS, clinical (Simple Clinical Colitis Activity Index, SCCAI) and laboratory parameters (CRP, FC) were assessed during anti-TNF therapy at week 0, 2, 6, and 12 in patients with active UC (SCCAI ≥ 5) and an increased bowel wall thickening (BWT) at baseline. Threshold for normal BWT was >4 mm for sigmoid colon and >3 mm for the descending colon. Results: Within the study population, 29% (65/224) of patients received an anti-TNF therapy (adalimumab, infliximab, or golimumab) at least at one time during the study. Mean disease duration was 7.56 ± 8.39 years. A majority of TNF-treated patients had an increased BWT at baseline, a high clinical activity, represented by an SCCAI of 9.52 ± 2.62, and an increased FC level ( n = 39, 1609 ± 1721.7 µg/g). The clinical activity changed significantly within 6 weeks for 61.5% ( n = 40) of the patients (9.08 ± 2.27 vs. 4.23 ± 4.00, p < 0.001). Of the patients with anti-TNF therapy at baseline and Week 6 ( n = 44) 47.7% ( n = 21) experienced a normalisation and 34.1% ( n = 15) a reduction of BWT at sigmoid colon or descending colon already within 6 weeks upon anti-TNF therapy. Patients with an ongoing vascularisation at Week 6 and 12 had a significantly higher SCCAI compared with patients with no colour Doppler signal ( p < 0.001). Conclusions: We demonstrated that anti-TNF treatment results in normalisation/reduction of BWT in a majority of UC patients as early as 6 weeks after start of anti-TNF therapy. Consequently, GIUS is useful in early monitoring of therapy response to anti-TNF therapy in UC patients enabling a non-invasive, easy, and repeatable means of tight control in daily practice. References 1. Colombel J-F, Panaccione R, Bossuyt P, et al . Effect of tight control management on Crohn's disease (CALM): a multicentre, randomised, controlled phase 3 trial. Lancet 2017;390. doi:10.1016/S0140-6736(17)32641-7 2. Kucharzik T, Wittig BM, Helwig U, et al . Use of intestinal ultrasound to monitor Crohn's disease activity. Clin Gastroenterol Hepatol 2017;15:535–42. 3. Kucharzik T, Maaser C, Helwig U, et al. Monitoring response to adalimumab therapy in Crohn's disease patients by bowel ultrasound: sub-analysis from TRUST. J Crohns Colitis 2018; Abtract P424.